2
$\begingroup$

How would I go about reducing the complicated-looking expression $$ \sqrt[3]{19\sqrt{5} + 56} + \frac{11}{\sqrt[3]{19\sqrt{5} + 56}} $$ to show that it is equal to 7?

I came across the complicated expression while calculating the single real solution for the cubic equation $$ z^3 - 33 z - 112 = 0 $$

Using that cubic equation, I can show that $ z = 7 $ satisfies it and that a standard way of solving cubic equations shows that there is only a single real root and that its value is equal to the complicated expression, which is a very roundabout way of proving that the complicated expression is equal to 7. But what if I didn't know about the cubic equation? Is there a more direct way of reducing the complicated expression to a simpler one?

$\endgroup$
  • 4
    $\begingroup$ Take the power 3 of this expression, using binomial formula $(a+b)^3$... $\endgroup$ – Jean Marie Feb 25 '17 at 21:56
  • $\begingroup$ Note that if $p+q+r=0$ then $p^3+q^3+r^3=3pqr$ - you can use this to get rid of the cube roots by taking the two components as $p, q$ and the sum as $p+q=-r$. $\endgroup$ – Mark Bennet Feb 25 '17 at 22:16
4
$\begingroup$

I'll outline the basic method to simplify$$\sqrt[3]{56+19\sqrt{5}}+\dfrac {11}{\sqrt[3]{56+19\sqrt{5}}}\tag{1}$$ To simplify the nested radical, note that we have this general outline:$$\sqrt[n]{A+B\sqrt[m]{C}}=a+b\sqrt[m]{C}\tag{2}$$ So therefore, we have$$\begin{align*}\sqrt[3]{56+19\sqrt{5}} & =a+b\sqrt{5}\\56+19\sqrt{5} & =\underbrace{(a^3+15ab^2)}_{56}+\underbrace{(3a^2b+5b^3)}_{19}\sqrt{5}\end{align*}$$ So we get this system of equations:$$\begin{align*} & a^3+15ab^2=56\\ & 3a^2b+5b^3=19\end{align*}\tag{3}$$ $(3)$ has real solutions as $(a,b)=\left(\dfrac 72,\dfrac 12\right)$ so$$\sqrt[3]{56+19\sqrt{5}}=\dfrac {7+\sqrt5}2\tag4$$ Using $(4)$, and through some algebraic manipulations, we have$$\begin{align*}\color{blue}{\sqrt[3]{56+19\sqrt5}}+\dfrac {11}{\color{red}{\sqrt[3]{56+19\sqrt{5}}}} & =\color{blue}{\dfrac {7+\sqrt{5}}2}+\dfrac {11}{\color{red}{\frac {7+\sqrt{5}}2}}\\ & =\dfrac {7+\sqrt{5}}{2}+\dfrac {22}{7+\sqrt{5}}\\ & =\dfrac {7+\sqrt{5}}2+\dfrac {22(7-\sqrt5)}{44}\\ & =\dfrac {7+\sqrt5}2+\dfrac {7-\sqrt5}2\\ & =\boxed 7\end{align*}$$ Just like what you got!

$\endgroup$
2
$\begingroup$

One possibility is to factor $19\sqrt{5}+56$ in the ring of integers of the field $\mathbb{Q}(\sqrt{5})$, which gives $$ 19\sqrt{5}+56 = \left(\frac{1+\sqrt{5}}2 \right)^3(4-\sqrt5)^3 $$ and now it is easy to continue.

If you wonder how I arrived to this factorization, it is known that the ring of integers of $\mathbb Q(\sqrt{5})$ is a unique factorization domain, the norm of $19\sqrt{5}+56$ in this field is $11^3$ so this implies that it is divisible by either $4-\sqrt{5}$ or $4+\sqrt{5}$ which are the primes of $\mathbb Q(\sqrt{5})$ under $11$. After performing the division, the result is a unit, and so it is of the form $\pm (\tfrac{1+\sqrt{5}}{2})^k $, as $\tfrac{1+\sqrt{5}}{2}$ is the fundamental unit of $\mathbb Q(\sqrt{5})$.

$\endgroup$
1
$\begingroup$

Using $a=\sqrt[3]{19\sqrt5+56}$ and $b=\frac{11}{\sqrt[3]{19\sqrt5+56}}$ and $u=a+b$, we have $$ \begin{align} a^3+b^3 &=19\sqrt5+56+\frac{1331}{19\sqrt5+56}\\ &=\frac{6272+2128\sqrt5}{56+19\sqrt5}\\[6pt] &=112 \end{align} $$ Thus, $$ \begin{align} &112\\ &=a^3+b^3\\ &=(a+b)\left(a^2-ab+b^2\right)\\ &=(a+b)\left((a+b)^2-3ab\right)\\ &=u(u^2-33) \end{align} $$ Noting that for $x\lt\sqrt{11}$, $$ \begin{align} x^3-33x-112 &\le22\sqrt{11}-112\\ &\lt0 \end{align} $$ and for $x\ge\sqrt{11}$, $x^3-33x-112$ is increasing, we see that $x^3-33x-112=0$ has only one real solution, and that is $x=7$.

Therefore, $\sqrt[3]{19\sqrt5+56}+\frac{11}{\sqrt[3]{19\sqrt5+56}}=a+b=u=7$.

$\endgroup$
0
$\begingroup$

But what if I didn't know about the cubic equation?

As long as you have a reasonable suspicion that the expression might be rational, the polynomial it satisfies can be derived rather easily. Let:

$$ x = \sqrt[3]{19\sqrt{5} + 56} + \frac{11}{\sqrt[3]{19\sqrt{5} + 56}} $$

Then using $(a+b)^3=a^3+b^3+3ab(a+b)\,$ and $(56+19\sqrt{5})(56-19\sqrt{5})=1331=11^3\,$:

$$ \require{cancel} \begin{align} x^3 & = 19\sqrt{5} + 56 + \frac{11^3}{19\sqrt{5} + 56} + 3 \cdot \cancel{\sqrt[3]{19\sqrt{5} + 56}} \cdot \frac{11}{\cancel{\sqrt[3]{19\sqrt{5} + 56}}} \cdot x \\ & = 56+ \cancel{19\sqrt{5}} + 56 - \cancel{19\sqrt{5}} + 33x \\ & = 112 + 33x \end{align} $$

By the rational root theorem, the equation $x^3-33x-112=0$ can only have rational roots that are integer divisors of $112=2^4\cdot 7\,$. Obviously $\pm 1$ do not satisfy the equation, and even roots can be eliminated by comparing the powers of $2$ between the terms, which leaves $\pm 7\,$ to try.

$\endgroup$
  • $\begingroup$ Wish the downvoter had left a comment why. $\endgroup$ – dxiv Feb 26 '17 at 21:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.